Integrated Learning through Play - Šagud, Mirjana (Array, 2010)
As a dominant (yet unfortunately not frequent enough) activity and a natural form of learning in an institutionalised and family early education, game is often considered a medium of content and integrated learning of a preschool child only at a declarative level. Varying and trying different relationships that a child has perceived in reality, certain forms of behaviour necessary for their later active participation in the world of adults are created. Traditional preschool institutions are often directed towards teaching the fragmented, routine and partial content (with a dominant analytical approach to learning) that greatly resembles school subjects. In correspondence with this is the education of preschool teachers that is directed towards developing isolated and disconnected practical and professional competencies during their initial professional development. In the educational practice, there are frequently situations of instrumentalization of game with the aim of teaching disintegrated teaching approaches (organising children's game with the aim to learn specialised content in the field of speech, beginning mathematics notions, physical activity, etc.). On the other hand, contemporary learning paradigms of constructing and co-constructing knowledge, accepting and satisfying individual differences between children, should enable different levels of integrating content within a complete and integrated approach to early education.